Lively cities : reconfiguring urban ecology - Barua, Maan, 1982- (University of Minnesota Press, 2023)
"Lively Cities departs from conventions of urban studies to argue that cities are lived achievements forged by a multitude of entities-human and nonhuman-that make up the material politics of city making. Generating fresh conversations between posthumanism, postcolonialism, and political economy, Barua reveals how these actors shape, integrate, subsume, and relate to urban space in fascinating ways"--